Danu Kertih sebagai Upaya Pelestarian Air Danau Batur (Kajian Teo-Sosio) - I Wayan Titra Gunawijaya; Putu Agustiantini (Jnanasiddhanta : Jurnal Teologi Hindu, 2022)
Preservation can be done through the efforts of religious rituals which are a supra-empiricalaspect. Ampek is an effort to further increase public awareness of the environment as well as aform of implementation of religious teachings. Danu Kertih is part of a ceremony to rebuild theLake environment with the hope of regenerating the natural ecosystem. Through a qualitativeapproach and data collection with various approach techniques such as determining informantsby snowball, collecting data through observations presented in the form of descriptions. Theresults of the study explain Danu Kertih as an effort to restore ecosystems in nature, especiallylakes. Danu Kertih as an effort to purify the Great Bhuana, namely the lake, water and itsecosystem, thus the community will continue to preserve the lake by not throwing garbage in thelake, with the increase in lake water after the Danu Kertih ceremony will certainly have an impacton all Subaks in Bali. In addition to having an impact on the surrounding environment, it also hasan impact on communities outside Batur, namely ethanies around the flow of water sourced fromLake Batur. Through abundant water, it is hoped that the plants planted by farmers will be fertileand produce abundant results.